A shortcut through time : the path to the quantum computer - Johnson, George, 1952 January 20- (New York : Alfred A. Knopf : Distributed by Random House, 2003)
Publisher's description: The first book to prepare us for the next big--perhaps the biggest--breakthrough in the short history of the cyberworld: the development of the quantum computer. The newest Pentium chip driving personal computers packs 40 million electronic switches onto a piece of silicon the size of a thumbnail. It is dramatically smaller and more powerful than anything that has come before it. If this incredible shrinking act continues, the logical culmination is a computer in which each switch is composed of a single atom. And at that point the miraculous--the actualization of quantum mechanics--becomes real. If atoms can be harnessed, society will be transformed: problems that could take forever to be solved on the supercomputers available today would be dispatched with ease. Quantum computing promises nothing less astonishing than a shortcut through time. In this book, the award-winning New York Times science writer George Johnson first takes us back to the original idea of a computer--almost simple enough to be made of Tinkertoys--and then leads us through increasing levels of complexity to the soul of this remarkable new machine. He shows us how, in laboratories around the world, the revolution has already begun. Writing with a brilliant clarity, Johnson makes sophisticated material on (and even beyond) the frontiers of science both graspable and utterly fascinating, affording us a front-row seat at one of the most galvanizing scientific dramas of the new century.
"Simple electric brain machines and how to make them" -- Tinkertoy logic -- Playing with mirrors -- A shortcut through time -- Shor's algorithm -- Breaking the code -- Invisible machines -- Counting with atoms -- Quantum secrecy -- The hardest problem in the universe.
Includes bibliographical references (p. [175]-191) and index.
Keywords: Quantum computers